AMPK variant, a candidate of novel predictor for chemotherapy in metastatic colorectal cancer: A meta‐analysis using TRIBE, MAVERICC and FIRE3. Issue 8 (26th March 2019) - Tokunaga, Ryuma; Cao, Shu; Naseem, Madiha; Battaglin, Francesca; Lo, Jae Ho; Arai, Hiroyuki; Loupakis, Fotios; Stintzing, Sebastian; Puccini, Alberto; Berger, Martin D; Soni, Shivani; Zhang, Wu; et al.
Abstract : AMP‐activated protein kinase (AMPK) is a key sensor of energy homeostasis and regulates cell metabolism, proliferation and chemotherapy/radiotherapy sensitivities. This study aimed to explore the relationship between the AMPK pathway‐related single nucleotide polymorphisms (SNPs) and clinical outcomes in patients with metastatic colorectal cancer (mCRC). We analyzed a total of 884 patients with mCRC enrolled in three randomized clinical trials (TRIBE, MAVERICC and FIRE‐3: where patients were treated with FOLFIRI, mFOLFOX6 or FOLFOXIRI combined with bevacizumab or cetuximab as the first‐line chemotherapy). The association between AMPK pathway‐related SNPs and clinical outcomes was analyzed across the six treatment cohorts, using a meta‐analysis approach. Our meta‐analysis showed that AMPK pathway had significant associations with progression‐free survival (PFS; p  < 0.001) and overall survival (OS; p  < 0.001), but not with tumor response (TR; p  = 0.220): PRKAA1 rs13361707 was significantly associated with favorable PFS (log HR = −0.219, SE = 0.073, p  = 0.003), as well as PRKAA1 rs10074991 (log HR = −0.215, SE = 0.073, p  = 0.003), and there were suggestive associations of PRKAG1 rs1138908 with unfavorable OS (log HR = 0.170, SE = 0.083, p  = 0.041), and of UBE2O rs3803739 with unfavorable PFS (log HR = 0.137, SE = 0.068, p  = 0.042) and OS (log HR = 0.210, SE = 0.077, p  = 0.006), although these results were not significant after false discovery rate adjustment. AMPK pathway‐related SNPs may be predictors for chemotherapy in mCRC. Upon validation, our findings would provide novel insight for selecting treatment strategies. Abstract : What's new? Using data from three randomized clinical trials (TRIBE, MAVERICC, and FIRE‐3), this study investigates whether AMP‐activated kinase (AMPK)‐associated genomic markers are predictors for clinical outcome in patients with metastatic colorectal cancer. The authors find two single‐nucleotide polymorphisms (PRKAA1 rs13361707 and PRKAA1 rs10074991) that predicted favorable outcome after chemotherapy while two others (PRKAG1 rs1138908 and UBE2O rs3803739) predicted unfavorable outcome although the latter result did not reach significance. Targeting AMPK in addition to chemotherapy could be beneficial for some patients with metastatic colorectal cancer.